Actionable emotion detection in context-aware systems - Suni Lopez, Franci (2018)
Finally, I would like to thank in a special way to the National Council for Science, Technology and Technological Innovation (CONCYTEC-PERU) and to the National Fund for Scientific Development, Technological and Technological Innovation (FONDECYTCIENCIACTIVA), which through the Management Agreement 234-2015-FONDECYT have allowed the grant and financing of my studies in the Master Program in Computer Science at Universidad Cat´olica San Pablo (UCSP).